Property maintenance and mangement at Putra World Trade Center / Zaizul Bhary Zakaria ... [et al .] - Zakaria, Zaizul Bhary; Abd Jalil, Mohd Johan Ariffin; Ismail, Hassan; Abdullah, Noridah; Yaakub, Siti Rahayu; Jaafar, Maizatul Zana (2002)
Building maintenance management is one of the important aspects in any property management. The understanding of the building maintenance and its filed area is a must for a professional Building Surveyor.